Characterization of Plukenetia volubilis L. fatty acid-based alkyd resins. (February 2020) - Hadzich, Antonella; Gross, G. Alexander; Leimbach, Martin; Ispas, Adriana; Bund, Andreas; Flores, Santiago
Abstract: Fatty acid-based alkyd resins prepared with different amounts of glycerol and pentaerythritol were characterized. Sacha inchi oil and linseed oil (comparative purposes) were used as fatty acids' sources. FT-IR and 1 H NMR spectroscopy were done for alkyd structural verification. Alkyd resins were evaluated through physico-chemical (colour, density, viscosity) and thermal characterization. Film coating performance (drying, hardness, chemical resistance) was also studied. The oxidative crosslinking time tendency was corroborated by the quartz crystal microbalance (QCM) technique. Alkyd resins obtained with fatty acids from sacha inchi and linseed oils had similar properties. Results indicated that lighter resins can be obtained from sacha inchi oil, whereas pentaerythritol increases viscosity and thermal stability, and retards drying time of fatty-acid based alkyd resins. Graphical abstract: Image 1 Highlights: Sacha inchi-based alkyds had an equivalent behaviour to linseed oil-based ones. Final colour of sacha inchi fatty acid-based alkyd resins was lighter. Pentaerythritol retarded oxygen uptake during crosslinking process. Pentaerythritol increased viscosity and thermal stability of alkyds. Sacha inchi oil's fatty acids are new alternative sources for resin formulation.